Activity involvement as an ecological asset: Profiles of participation and youth outcomes. - Johnson, Sara K. ; Agans, J. P. ; DeSouza, L. M.; Mueller, M. K.; Champigne, R.; Lerner, Richard M. (Tufts Archival Research Center, 2016)
Prior research has demonstrated that participation in out-of-school time activities is associated with positive and healthy development among adolescents. However, fewer studies have examined how trajectories of participation across multiple activities can impact developmental outcomes. Using data from Wave 3 (approximately Grade 7) through Wave 8 (approximately Grade 12) of the 4-H Study of Positive Youth Development, this study examined patterns of breadth in out-of-school time participation in activities and associated outcomes in positive youth development (PYD), Contribution to self and community, risk behaviors, and depressive symptoms. We assessed 927 students (on average across waves, 65.4 % female) from a relatively racially and ethnically homogeneous sample (about 74 % European American, across waves) with a mean age in Wave 3 of 12.98 years (SD = 0.52). The results indicated that high likelihood of participation in activities was consistently associated with fewer negative outcomes and higher scores on PYD and Contribution, as compared to low likelihood of participation in activities. Changes in the breadth of participation (in particular, moving from a high to a low likelihood of participation) were associated with increased substance use, depressive symptoms, and risk behaviors. Limitations of the current study, implications for future research, and applications to youth programs are discussed.